Pelaksanaan Strategi Komunikasi Badan Pelayanan Terpadu dan Penanaman Modal dalam Menerapkan Kebijakan Sistem One Stop Service pada Masyarakat Kota Pekanbaru: Penelitian - Syahrial; Rian Prayudi Saputra; Maya Intan Pratiwi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
One Stop Service (OSS) is a government program aimed at improving public services, streamlining licensing and non-licensing bureaucracy, and promoting good governance. Based on the research findings, the communication strategy of the Integrated Licensing and Investment Agency (BPTPM) of Pekanbaru City in implementing the OSS system includes planning communicators and communication targets, planning the audience, crafting communication messages, and selecting appropriate media for delivering the OSS policy to the public. Business licensing procedures in Riau Province must comply with existing regulations, namely Regional Regulation No. 8 of 2012 on Nuisance Permit Retribution and Regional Regulation No. 3 of 2002 on Public Entertainment. Investment opportunities in Riau include the Tenayan Industrial Zone, the development of Lembah Sari Artificial Lake/Bandar Khayangan, and the construction of a goods/cargo terminal.